2012
DOI: 10.1186/1756-9966-31-68
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers associated with outcome and metastasis in human pancreatic cancer

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) is a heterogeneous cancer in which differences in survival rates might be related to a variety in gene expression profiles. Although the molecular biology of PDAC begins to be revealed, genes or pathways that specifically drive tumour progression or metastasis are not well understood.MethodsWe performed microarray analyses on whole-tumour samples of 2 human PDAC subpopulations with similar clinicopathological features, but extremely distinct survival rates afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 47 publications
1
62
0
1
Order By: Relevance
“…In human studies, gastric MUC13 is found to be down-regulated after H. pylori infection [21] and has been shown to be aberrantly expressed in gastrointestinal cancers [22]. ITGB5 is up-regulated in pancreatic adenocarcinoma [14],[23], and its repression impairs angiogenesis both in vitro and in vivo [24]. We have previously found that the expression of porcine MUC13 and MUC4 was down-regulated in IPEC-J2 cells post infection with the same F4ac ETEC strain, and the expression of ITGB5 was not significantly decreased [5].…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, gastric MUC13 is found to be down-regulated after H. pylori infection [21] and has been shown to be aberrantly expressed in gastrointestinal cancers [22]. ITGB5 is up-regulated in pancreatic adenocarcinoma [14],[23], and its repression impairs angiogenesis both in vitro and in vivo [24]. We have previously found that the expression of porcine MUC13 and MUC4 was down-regulated in IPEC-J2 cells post infection with the same F4ac ETEC strain, and the expression of ITGB5 was not significantly decreased [5].…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether FRA-1 expression changed during the progression of pancreatic cancer, we evaluated the data series GSE42952, which includes tumor stage and some matched primary and metastatic tumors. FOSL1 expression was plotted for each tumor stage identified within the data set, ignoring absent calls (Figure 5C) [28, 30]. For metastatic sites we differentiated between the identified liver or peritoneal metastatic site.…”
Section: Resultsmentioning
confidence: 99%
“…17,22,33,[43][44][45] It is particularly noteworthy that basigin-targeted therapy 46 and EGFR-targeted therapy (reviewed in ref 47) have been investigated for pancreatic cancer, underscoring the importance of identifying novel cell-surface proteins as potential targets for pancreatic cancer therapy.…”
Section: Discussionmentioning
confidence: 99%